Building Trust in the Classroom: A Conceptual Model for Teachers, Scholars, and Academic Developers in Higher Education - Felten, Peter; Forsyth, Rachel; Sutherland, Kathryn A. (Teaching and Learning Inquiry, 2023)
The quality of student-teacher classroom interactions is important to learning, belonging, and success, particularly for students from groups that have been historically excluded from or marginalized in higher education. The literature commonly asserts that one necessary part of high-quality educational interactions (whether in person or online) is trust, but several scholars note that trust has not been systematically explored by scholars of higher education teaching and learning. In this paper, we propose a conceptual framework for identifying and describing teacher-initiated “trust moves” in the classroom, based on both the literature and interviews with teaching faculty in varied contexts. In doing this, we hope to provide a practical resource for teachers to reflect on possible approaches for building trust with students in their own classrooms—and for scholars and academic developers who wish to study or support these efforts. Click here to read the corresponding ISSOTL blog post.